2014
DOI: 10.1371/journal.pone.0088979
|View full text |Cite
|
Sign up to set email alerts
|

GLA-AF, an Emulsion-Free Vaccine Adjuvant for Pandemic Influenza

Abstract: The ongoing threat from Influenza necessitates the development of new vaccine and adjuvant technologies that can maximize vaccine immunogenicity, shorten production cycles, and increase global vaccine supply. Currently, the most successful adjuvants for Influenza vaccines are squalene-based oil-in-water emulsions. These adjuvants enhance seroprotective antibody titers to homologous and heterologous strains of virus, and augment a significant dose sparing activity that could improve vaccine manufacturing capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 31 publications
(28 reference statements)
1
32
0
1
Order By: Relevance
“…GLA adjuvant formulations have been used with experimental vaccines for influenza, HIV (29), respiratory syncytial virus (RSV) (30), leishmaniasis (31), malaria (32), and leprosy (33) in addition to TB (34,35). Many of these vaccines using GLA formulations have also resulted in protection in preclinical animal models, including mice (34)(35)(36), ferrets (37,38), guinea pigs (34,35,39), cotton rats (30), and hamsters (40), against infectious challenge.…”
Section: Et Al Have Shown a Transient Increase In Ifn-␥ From Cd4mentioning
confidence: 99%
“…GLA adjuvant formulations have been used with experimental vaccines for influenza, HIV (29), respiratory syncytial virus (RSV) (30), leishmaniasis (31), malaria (32), and leprosy (33) in addition to TB (34,35). Many of these vaccines using GLA formulations have also resulted in protection in preclinical animal models, including mice (34)(35)(36), ferrets (37,38), guinea pigs (34,35,39), cotton rats (30), and hamsters (40), against infectious challenge.…”
Section: Et Al Have Shown a Transient Increase In Ifn-␥ From Cd4mentioning
confidence: 99%
“…In this study we employed a whole blood assay (WBA) to study the ontogeny of cytokine responses to four TLRAs: monophosphoryl lipid A (MPLA; TLR4), an aqueous formulation the novel glucopyranosyl lipid antigen (GLA-AF; TLR4) [33, 34], resiquimod (R848; TLR7/8) and CpG oligonucleotide ODN 2395 (TLR9). Although both MPLA and GLA are based on the core lipid A of LPS, there are important differences between these two molecules, including that the latter is synthetic [34].…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have shown that these types of antibodies can be induced following heterologous primeboost vaccination and by using vaccine adjuvants that broaden heterosubtypic Ab responses (Buricchi et al, 2013; Chiu et al, 2013; Li et al, 2013). Thus, to enrich for cross-reactive Abs, mice were immunized with rHA isolated from 2 Group 1 HA viruses, VN1203 and CA07 virus, in the presence of the TLR4 adjuvant GLA-SE, which increases antibody repertoire diversity and enhances protection against heterosubtypic strains of H5N1 virus in mice and ferrets (Clegg et al, 2014; Clegg et al, 2012; Wiley et al, 2011). Antisera were then tested for their ability to bind to their cognate antigen as well as for cross-binding to heterologous Group 1 and Group 2 rHA proteins.…”
Section: Resultsmentioning
confidence: 99%